Co-design of a paediatric oncology medicines database (ProCure) to support complex care provision for children with a hard-to-treat cancer - Mazariego, Carolyn G.; McKay, Skye; Tyedmers, Elijah; Kelada, Lauren; McGill, Brittany C.; Daly, Rebecca; Wakefield, Claire E.; Ziegler, David S.; Taylor, Natalie (Frontiers in Medicine, 2024)
Objectives: Paediatric oncologists often encounter challenges when seeking compassionate access to off-label therapies for their patients. This study employed implementation science and codesign techniques to develop the ProCure medicines database, with the goal of streamlining the application process and addressing identified barriers in paediatric oncology.: This study utilised an exploratory qualitative research design. Seventeen healthcare providers, including oncologists, nurse consultants, and allied health professionals, participated in semi-structured interviews guided by the Consolidated Framework for Implementation Research (CFIR) and a visual process map aid. Deductive qualitative data analysis, according to CFIR constructs, identified key barriers and facilitators. Collaborative design sessions engaged multidisciplinary teams to develop the ProCure beta version.Results: Barriers to off-label therapy access included resource-intensive applications, time sensitive decision-making, and complex pharmaceutical information. Facilitators included Drug Access Navigators, Molecular Tumour Boards, and a multi-disciplinary approach. ProCure addressed end-user needs by centralising medicines information. Additional features suggested by healthcare providers included blood-brain-barrier penetrability data and successful application examples.ProCure represents a promising solution to the challenges paediatric oncologists face in accessing off-label therapies. By centralising information, it simplifies the application process, aids decision-making, and promotes a collaborative approach to patient care. The database's potential to streamline and enhance off-label therapy access underscores its relevance in improving paediatric oncology practice. Further research and implementation efforts are warranted to assess ProCure's real-world impact and refine its features based on user feedback.